APPLICATION OF FRUIT BAGGING, SANITATION, AND YELLOW STICKY TRAP TO CONTROL THRIPS ON MANGOSTEEN - Affandi Affandi; D. Emilda; M. Jawal A.S (Indonesian Agency for Agricultural Research and Development, 2008)
Scars on mangosteen fruits caused by thrips are the most prominent constraint in Indonesian export of mangosteen. Most of the exported mangosteen are rejected due to scar appearance. This research aimed to study the effects of fruit bagging, sanitation, and sticky trap application on the scar intensity on mangosteen. The research was conducted at a farmer's polycultured mangosteen orchard in Lima Puluh Kota, West Sumatra, Indonesia from September 2006 to February 2007. The mangosteen trees were cultured with cacao and coconut. To study the effects of bagging on the number of scars, the fruits were individually bagged at different time points starting from the time of calyx falling down (0) followed at 2, 4, 6, 8, 10, 12, and 14 weeks later. Each treatment was replicated six times. The experiment of sanitation (SNT) and yellow fluorescent sticky trap (YST) application was designed in a completely randomized design with six replications, except for the control which was replicated only three times. Four treatments studied were SNT, YST, combination of SNT+YST, and control. The sanitation was applied by removing all weeds under the canopy of mangosteen trees followed with soil tillage and fogging. The sticky trap was nailed on woody sticks and placed on 3 m above the ground at four different positions around the tree canopy. Parameters observed were the percentage and intensityof scars and number of thrips caught on the sticky traps. The results showed that application of early bagging, SNT, YST, and SNT+YST were effective to reduce intensity and percentage of scars. However, combination of SNT+YST demonstrated the best results in reducing the intensity and percentage of scars by 32.14% and 42.82%, respectively. Combination of SNT+YST also drastically decreased thrips population as indicated by thelow number of thrips catched after five biweekly observations. Since the fifth observation, the thrips population was low (less than 5 thrips catched per sticky trap) and far below the economic threshold. The present study implies the importance of early fruit bagging, sanitation, and sticky trap application in protecting mangosteen fruits from scars.